Formulation and characterization of fast-dissolving tablet of promethazine theoclate - Sharma, Shailesh; Gupta, G D (Asian Journal of Pharmaceutics (AJP), 2014)
Fast-dissolving tablets (FDT) of promethazine theoclate were prepared by direct-compression method after incorporating superdisintegrants Ac-Di-Sol, Sodium Starch Glycolate (SSG), and Crospovidone in different concentrations. Nine formulations having superdisintegrants at different concentration levels were prepared to assess their efficiency and critical concentration level. Different types of evaluation parameters for tablets were used. Tablets containing Ac- Di- Sol showed superior organoleptic properties, along with excellent in vitro and in vivo dispersion time and drug release, as compared to other formulations. Key words: Direct compression, promethazine theoclate, superdisintegrant